A rare case of obstructive ileus due to ileal pouch torsion: a case report and systematic review - P. Vrakopoulou, Gavriella Zoi; Matiatou, Maria A.; Larentzakis, Andreas V.; Zografos, George C.; Toutouzas, Konstantinos G. (International Surgery Journal, 2020)
Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) has become the standard surgical treatment for ulcerative colitis patients. Among others, it is important for clinicians to be aware of a rare, though urgent situation, the ileal pouch torsion. A high degree of suspicion is essential as obstruction due to pouch torsion is not likely to resolve conservatively. Delay in diagnosis and treatment can lead to pouch jeopardy and life-threatening complications. The aim of this study was to present a systematic review of the literature combined with the presentation of a case report of our department regarding this rare entity. A systematic literature review according to QUORUM guidelines was conducted in July 2019 using MEDLINE, SCOPUS, and COCHRANE databases. We included studies reporting pouch torsion after IPAA in English or German language with no restriction regarding publication time. Outcomes after different treatment options, such as operative pouch detorsion, and/or pouchpexy, and/or pouch reconstruction, and/or end-ileostomy through laparoscopic or open procedures were evaluated. We identified 170 publications. After duplicates and irrelevant articles have been excluded, 25 publications remained for full-text review. Finally, 12 articles were included in this systematic review, concerning 14 cases. To the best of our knowledge, this is the first comprehensive systematic review on this topic to date.